Ciliwung Care Community Management Policy (Mat Peci) in Sekolah Sungai Ciliwung Program, Srengseng Sawah, Jagakarsa - Dipa Teruna Awaloedin; Rizki Nurul Nugraha; Padri Achyarsyah (Westscience Press, 2023)
The Ciliwung River crosses various forms of human activity, from agriculture, fisheries, residential areas, plantations, and transportation to tourism industry activities. The Ciliwung River spans from upstream to downstream which has a lot of tourism potential, one of which is the Ciliwung River School (SSC) which is managed by the Ciliwung Concerned Community and the Environment (Mat Peci). Amid the changes that have hit Indonesia from Covid-19 to post-Covid-19, many policy changes have occurred in the tourism industry. In this study, the author tries to see how the Ciliwung River school area applies policies during a pandemic and after a pandemic. The method used in this study uses primary data taken directly from the Ciliwung River School while using a descriptive qualitative analysis approach, with data sources in the form of secondary data obtained from previous research and related agencies. The results of the study show that there is a Ciliwung River School program that has handling and management of policies that are well-owned during a pandemic and also after a pandemic, this is implemented to be able to continue in managing existing ecotourism along the Ciliwung river flow. can increase awareness and concern for teenagers, surrounding youth organizations also help protect the environment and learn how to manage it.